Imperialism and fascism intertwined: a materialist analysis of the games industry and reactionary gamers - Hammar, Emil (Gamevironments, 2020)
This article paves way for a materialist analysis of the games industry as 21st century imperialism that is economically and culturally structured to cultivate anti-democratic norms that lead to fascist movements against those who question or seek to change the status quo. While much research has studied the politics of reactionary movements in gaming cultures, few have paid attention to the relation between the games industry as part of an imperialist economic system, the chauvinistic ideals symptomized in their cultural products, and the reactionist consumer audiences they attract and cultivate. As I argue, the economic structure of the industry as 21st century imperialism leads to perpetual anti-democratic crises that are maintained by reactionary forces that cultivate, attract, and form fascist grassroots organization. To conceptualize this dynamic, I invoke the labor aristocracy theory as suggested by Friedrich Engels and V.I. Lenin. This theory helps highlight the material basis from which consumers of digital games are bribed to become ideologically aligned with the chauvinism that the imperialist nature of the games industry is justified by. I also invoke W.E.B. Du Bois’ concept of a public and psychological wage to highlight the chauvinistic tendencies that the games industry cultivates via their products and marketing, in which the lack of democratic and equitable representation provides the reactionary consumers a sense of superiority. Together, these approaches account for the economic and cultural bases of both the games industry and its reactionary consumers. By anchoring my analysis in critical theories on imperialism and race, the article identifies the root causes of organized harassment and chauvinism in game cultures, as well as how the industry as 21st century imperialism benefits from and is protected by these forces of reaction.